Juventudes e ensino médio: a percepção de estudantes de Miracema do Tocantins - Silva, Rita de Cássea Coronheira (Universidade Federal do Tocantins, 2021)
This research deals with a work carried out in the Professional Graduate Program in Education (PPPGE / UFT), in the Research Line: Specific Curricula of Steps and Modalities of Education. It problematizes the thinking of the youths about the teaching proposal they are receiving, about being a high school student in the context of contemporaneity and in the perspective of youth protagonism, a project embraced by the school object of our study. The objective is to raise students' perceptions about full-time high school offered at a public school in Miracema (TO). The aim of this research was to highlight a brief history of teaching in Brazil and its educational guidelines, aimed at the integral public high school, the project of youth protagonism, and the importance of digital technologies in the educational context, reflecting, after all, that youths are these and how they think about their relationship with school, with learning. This proposal seeks to discuss education from the students' speeches. In general, studies on youth and education investigate numerous problems, but rarely have their voice. The exploratory and descriptive research, with qualitative and quantitative approach, uses as data collection techniques: questionnaires with open and closed questions; focus group; and semi-structured interview. From the study it is possible to state that the teaching model offered full time in the school in question is considered of quality, although the demand is still lower than the supply. What translates, is that students are focused on studies, see this step as a gateway to the university, claim that the Young School in Action, prepares them for life. Although the use and handling of new technologies are invoked as' Achilles' heel ', in this respect, advances are slow, contradicting the rapidity with technological evolution, trampling us. The search result generated an e-book as the end product. This brings the experience of research and reflections on the speech of these youths regarding the school, the ways of teaching and learning, the use of technologies and the project youth protagonism. This product can be accessed by schools, teachers, students, managers, thus contributing to thinking about education and high school in contemporary times